2014
DOI: 10.1021/bi500585u
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of the RIPoptosome Core Reveals a Helical Assembly for Kinase Recruitment

Abstract: Receptor interaction protein kinase 1 (RIP1) is a molecular cell-fate switch. RIP1, together with Fas-associated protein with death domain (FADD) and caspase-8, forms the RIPoptosome that activates apoptosis. RIP1 also associates with RIP3 to form the necrosome that triggers necroptosis. The RIPoptosome assembles through interactions between the death domains (DDs) of RIP1 and FADD and between death effector domains (DEDs) of FADD and caspase-8. In this study, we analyzed the overall structure of the RIP1 DD/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(83 reference statements)
1
21
0
Order By: Relevance
“…The extrinsic apoptotic pathway is regulated by the tumor necrosis factor (TNF) family, including FasL (CD9) and TNF‐α, which interact with the TNF‐receptor (TNF‐R) family molecules FAS (CD95), TNF‐R1, and TNF‐R2, respectively ,. Fas‐associated protein with death domain (FADD), an adaptor protein that bridges death receptor signaling and the caspase cascade, is indispensable for the induction of extrinsic apoptotic cell death . After treating MCF‐7 cells with certain concentrations of H‐RuBmp for 12 h, we found that H‐RuBmp dose‐dependently upregulated the expression of death receptor TNF‐R2, triggered apoptosis by recruiting FADD, and activated caspase‐8, caspase‐10 and tBid, the last of which links activation of the death receptor‐dependent and mitochondrial apoptotic pathways (Figure E).…”
Section: Resultsmentioning
confidence: 99%
“…The extrinsic apoptotic pathway is regulated by the tumor necrosis factor (TNF) family, including FasL (CD9) and TNF‐α, which interact with the TNF‐receptor (TNF‐R) family molecules FAS (CD95), TNF‐R1, and TNF‐R2, respectively ,. Fas‐associated protein with death domain (FADD), an adaptor protein that bridges death receptor signaling and the caspase cascade, is indispensable for the induction of extrinsic apoptotic cell death . After treating MCF‐7 cells with certain concentrations of H‐RuBmp for 12 h, we found that H‐RuBmp dose‐dependently upregulated the expression of death receptor TNF‐R2, triggered apoptosis by recruiting FADD, and activated caspase‐8, caspase‐10 and tBid, the last of which links activation of the death receptor‐dependent and mitochondrial apoptotic pathways (Figure E).…”
Section: Resultsmentioning
confidence: 99%
“…If RIPK3 acts as a kinase or may also modulate the stoichiometry of protein complexes by a presumed scaffold function is an intriguing question that needs to be addressed in the future. 24 , 61 …”
Section: Discussionmentioning
confidence: 99%
“…These clusters should rely on both DD/DD and DED/DED interactions among the DISC component proteins. Structural and biochemical studies on Fas/FADD and RIP1/FADD DD complexes have implicated helical assembly in DD/DD oligomerization (Esposito et al, 2010; Jang et al, 2014; Wang et al, 2010). However, despite structures of isolated DEDs, how DEDs oligomerize and interact with each other remained elusive due to lack of oligomeric structures (Bagneris et al, 2008; Eberstadt et al, 1998; Shen et al, 2015; Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%